SYSTEMY MIĘDZYNARODOWEGO PRAWA UPADŁOŚCIOWEGO - Prusak, Błażej (Wydział Prawa i Administracji UAM, 2007)
The dynamically increasing number of transnational corporations in the global economy determines, especially in crisis periods, the rise in the number of transnational bankruptcies. Recently there have been a number of spectacular transnational bankruptcies such as: Parmalat, Yukos, Daewoo. As a result, this issue attracts interests of both practitioners and theory makers. This paper presents five bankruptcy system proposals (universalism, territorialism, cooperative territoriality, modified universalism and Rasmussen’s corporate-charter contractualism). The author has conducted a comparative analysis o f the above mentioned systems showing their advantages and disadvantages and presented their implementation in practice.
SYSTEMS OF INTERNATIONAL BANKRUPTCY LAW